(untitled) (Global Journal of Medical Research, 2014)
Unmet need is defined as not using contraceptives despite expressed demand for limiting or spacing a child exists to varying degrees in virtually every developing country for various reasons. There is limited knowledge about the extent and associated factors of unmet need for family planning in the study area. Therefore this community based cross-sectional study was conducted. The overall unmet need for family planning was 41.5%. It was relatively lower among currently married women that 34.4% of currently married women had unmet need for family planning. More than 50% of the demand for family planning was not met. Factors like ethnicity, age of the participant, participant’s education, husband’s occupation, having discussion about family planning with partner in the last 6 months and gravidity were independent predictors of unmet need for family planning among currently married women. Efforts to be exerted were recommended in order to reduce this high rate of unmet need by focusing on those kebeles which Wolayta and Zeyse tribes live, older age, illiterates and those with high gravidity.